A woman who lost weight at the cost of her heartbeat. (1st August 2014) - Shah, Rushikesh; Bansal, Nidhi; Manocha, Divey
Abstract : With increasing prevalence of obesity worldwide, the number of patients undergoing bariatric surgery is also rising. Although the incidence of adverse outcomes associated with bariatric surgery has reduced, the physiological compensatory changes occurring after weight loss can lead to some unavoidable outcomes. One such condition is sinus bradycardia. The pathophysiology behind this is well studied but there is little awareness about this outcome. Sinus bradycardia in this clinical setting is generally asymptomatic and does not require any treatment. Extensive cardiac workup and unnecessary treatment can be avoided by increasing awareness among healthcare providers.